Amphiphilic zein hydrolysate as a delivery vehicle: The role of xanthophylls. (June 2017) - Wang, Yong-Hui; Wang, Jin-Mei; Guo, Jian; Wan, Zhi-Li; Yang, Xiao-Quan
Abstract: The aims of this study were to investigate the effect of xanthophylls (Xan) on the colloidal property and interfacial activity of zein hydrolysate (ZH), and the influence of Xan on the colloidal delivery capacity of ZH was also studied by the construction of emulsions and colloidal particles systems. The result indicated that compared with color-free ZH (CF-ZH), ZH was more sensitive to pH and showed obvious aggregation behavior at acidic pH. ZH exhibited lower critical micelle concentration compared with CF-ZH, suggesting the higher amphiphilic characteristic of ZH. The results from interfacial activity investigations showed that ZH exhibited higher interfacial activity compared with CF-ZH, and the thickness and intensity of the interfacial layer constituted by ZH was increased as a result of the existences of Xan. Compared with CF-ZH, the emulsions stabilized by ZH possessing smaller size and higher physical stability, and the curcumin nanoparticles fabricated in ZH solutions showed higher encapsulation efficiency, smaller particle size, better monodispersity and higher zeta potential. In conclusion, the presence of Xan in ZH obviously changed the colloidal property and improved interfacial activity and colloidal delivery capacity of ZH itself, and it endowed ZH with more extensive application prospects. Highlights: Colloidal behavior of zein hydrolysate was considerably influenced by Xan. Xan was successfully removed from zein hydrolysate under acidic pH condition. High surface activity of zein hydrolysate was resulted from the presence of Xan. Xan endowed zein hydrolysate with higher colloidal delivery capacity.